Duloxetine versus other anti-depressive agents for depression. - Cipriani, A; Koesters, M; Furukawa, T; Nosè, M; Purgato, M; Omori, I; Trespidi, C; Barbui, C (2012)
BACKGROUND: Although pharmacological and psychological interventions are both effective for major depression, in primary and secondary care settings antidepressant drugs remain the mainstay of treatment. Amongst antidepressants many different agents are available. Duloxetine hydrochloride is a dual reuptake inhibitor of serotonin and norepinephrine and has been licensed by the Food and Drug Administration in the US for major depressive disorder (MDD), generalised anxiety disorder, diabetic peripheral neuropathic pain, fibromyalgia and chronic musculoskeletal pain. OBJECTIVES: To assess the evidence for the efficacy, acceptability and tolerability of duloxetine in comparison with all other antidepressant agents in the acute-phase treatment of major depression. SEARCH METHODS: MEDLINE (1966 to 2012), EMBASE (1974 to 2012), the Cochrane Collaboration Depression, Anxiety and Neurosis Controlled Trials Register and the Cochrane Central Register of Controlled Trials up to March 2012. No language restriction was applied. Reference lists of relevant papers and previous systematic reviews were hand-searched. Pharmaceutical company marketing duloxetine and experts in this field were contacted for supplemental data. SELECTION CRITERIA: Randomised controlled trials allocating patients with major depression to duloxetine versus any other antidepressive agent. DATA COLLECTION AND ANALYSIS: Two review authors independently extracted data and a double-entry procedure was employed. Information extracted included study characteristics, participant characteristics, intervention details and outcome measures in terms of efficacy, acceptability and tolerability. MAIN RESULTS: A total of 16 randomised controlled trials (overall 5735 participants) were included in this systematic review. Of these, three trials were unpublished. We found 11 studies (overall 3304 participants) comparing duloxetine with one selective serotonin reuptake inhibitor (SSRI) (six studies versus paroxetine, three studies versus escitalopram and two versus fluoxetine), four studies (overall 1978 participants) comparing duloxetine with a newer antidepressants (three with venlafaxine and one with desvenlafaxine, respectively) and one study (overall 453 participants) comparing duloxetine with an antipsychotic drug which is also used as an antidepressive agent, quetiapine. No studies were found comparing duloxetine with tricyclic antidepressants. The pooled confidence intervals were rather wide and there were no statistically significant differences in efficacy when comparing duloxetine with other antidepressants. However, when compared with escitalopram or venlafaxine, there was a higher rate of drop out due to any cause in the patients randomised to duloxetine (odds ratio (OR) 1.62; 95% confidence interval (CI) 1.01 to 2.62 and OR 1.56; 95% CI 1.14 to 2.15, respectively). There was also some weak evidence suggesting that patients taking duloxetine experienced more adverse events than paroxetine (OR 1.24; 95% CI 0.99 to 1.55). AUTHORS' CONCLUSIONS: Duloxetine did not seem to provide a significant advantage in efficacy over other antidepressive agents for the acute-phase treatment of major depression. No differences in terms of efficacy were found, even though duloxetine was worse than some SSRIs (most of all, escitalopram) and newer antidepressants (like venlafaxine) in terms of acceptability and tolerability. Unfortunately, we only found evidence comparing duloxetine with a handful of other active antidepressive agents and only a few trials per comparison were found (in some cases we retrieved just one trial). This limited the power of the review to detect moderate, but clinically meaningful differences between the drugs. As many statistical tests have been used in the review, the findings from this review are better thought of as hypothesis forming rather than hypothesis testing and it would be very comforting to see the conclusions replicated in future trials. Most of included studies were sponsored by the drug industry manufacturing duloxetine. As for all other new investigational compounds, the potential for overestimation of treatment effect due to sponsorship bias should be borne in mind. In the present review no trials reported economic outcomes. Given that several SSRIs and the great majority of antidepressants are now available as generic formulation (only escitalopram, desvenlafaxine and duloxetine are still on patent), more comprehensive economic estimates of antidepressant treatment effect should be considered to better inform healthcare policy.